Product Standards and Firms’ Export Decisions - Fernandes, Ana M.; Ferro, Esteban; Wilson, John S. (Published by Oxford University Press on behalf of the World Bank, 2020)
Two novel datasets are used to estimate the effect of product standards on firms’ export decisions. The first covers all exporting firms in 42 developing countries. The second covers pesticide standards for 243 agricultural and food products in 80 importing countries over 2006–2012. The analysis shows that product standards affect significantly foreign market access. An increase in the stringency of standards in the destination country, relative to the exporting country, lowers firms’ probability of exporting, deters exporters from entering new markets, and fosters exit from existing markets. Smaller exporters are more affected in their market entry and exit decisions by the relative stringency of destination standards than larger exporters. Networks of other exporters from the same country can help overcome the negative effects of the relative stringency of destination standards on exporter entry and exit.